Workers' identities and paternalistic social relations in the cement industry. Calera Avellaneda S.A. (Olavarría) and Loma Negra S.A. (Villa Cacique-Barker) (Quinto Sol, 2022)
In the following article we present a comparison between two companies dedicated to the production of cement located in the province of Buenos Aires, Argentina. We examine the repetition of general features and unique characteristics of each of the cases, to then analyze the construction of certain social representations based on the labor relations that unfolded in this context.The company was conceived as a large patriarchal family, where the bosses exercised an authority that went far beyond the workplace, to extend to all aspects of daily life. The discourses that were constructed from them delimited certain representations, charged with a strong symbolic content, which collaborated to reinforce the labor relationship. In this way, it was shown that the integration of workers of different nationalities into the production system did not endanger the union, since the paternalistic labor and social policy managed to build a strong local identity, expressed in the feeling of belonging to the factory and its workers village.
Keywords: identities; paternalism; workers; cement industry